Analysis of the Causes of H&M Depression - Qu Yanrui (SHS Web of Conferences)
H&M is a company that manufacture clothes globally. However, in 2017-2020 years, H&M experienced difficulties globally. It adjusted its strategy in 2019 to cope with the situation and successfully recovered in global business, but the sustainability strategy it adopted failed to save its Chinese market and the group was forced out of Chinese in 2021. This research uses multiple approaches to analyse the strategy adopted by H&M and the successful outcome of it in the global market and the failure in the Chinese market. A PEST analysis is utilized to analyse the H&M group’s development path. H&M’s financial report from 2017 to 2023 is also analysed. This study also implements ESG analyses on the sustainability strategy adopted by H&M, aiming to solve its problems. The study found while the strategy lifted the global sales and profits from the difficulties during pandemic, it also complicated its relationship with the Chinese government during “Xinjiang cotton” event and was forced out of